2020
DOI: 10.1002/2050-7038.12466
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐area state estimation in a distribution network using Takagi‐Sugeno model estimated by Kalman filter

Abstract: Summary This study addressed the problem of multi‐area state estimation in a clustered distribution system. Distribution networks are inherently expansive and comprise a multitude of nodes. This issue increases the state estimation computation time and makes it inapplicable for control of sophisticated distribution networks. Multi‐area state estimation is a technique to reduce computation time while concerning computation accuracy. Many efforts are required to reach a perfect algorithm, followed by the optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The final results are compared to the integrated WLS method, and it is shown that execution time and computational complexity are improved in a data-based SE method. In [97], a novel machine learning-based distributed state estimation is proposed. Mathematical formulations of a data which exchanged in the boundary area are analyzed, and a new machine learning-based supervised learning is designed.…”
Section: Distribution State Estimation: Data-driven Approachesmentioning
confidence: 99%
“…The final results are compared to the integrated WLS method, and it is shown that execution time and computational complexity are improved in a data-based SE method. In [97], a novel machine learning-based distributed state estimation is proposed. Mathematical formulations of a data which exchanged in the boundary area are analyzed, and a new machine learning-based supervised learning is designed.…”
Section: Distribution State Estimation: Data-driven Approachesmentioning
confidence: 99%
“…Notably, this paradigm has found its way into the realm of smart grids [8], [9], leading to considerable speed enhancements in state estimation for large-scale systems [10]. Moreover, gradient-based techniques, often employing the Gauss-Newton method within each area, have been explored [11], along with the deployment of the Kalman filter [12]. While these advancements have undoubtedly marked progress, many existing multi-area state estimation methods rely heavily on geographical information for delineating network areas, often overlooking a distinct approach to zone partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic system state estimators developed decades ago, and diferent local and centralized schemes are found in scientifc literature, many of which are based on the Extended Kalman (EKF) approach [7][8][9][10][11][12][13][14] and some of its variants [15][16][17][18][19][20][21][22]. Despite its robust performance (in the presence of parametric errors and measurement noise) and well-known constructive design, these dynamic estimators have a heuristic tuning, not to mention the lack of formal robust convergence proofs.…”
Section: Introductionmentioning
confidence: 99%